Evaluation of Traditional Storage Materials for Improving Post-Harvest Shelf-Life and Quality of Turmeric (Curcuma longa) - Maharjan, Sanu Krishna; Dhakal, Sampada (Journal of the Institute of Agriculture and Animal Science, 2025)
Loss in post-harvest quality and shorter shelf-life of turmeric (Curcuma longa) rhizomes in Nepal are substantial due to a lack of proper storage practices, affecting both marketable rhizome and seed rhizome quality. To find an appropriate solution of this problem, the research was conducted using seven different storage materials- T1: Straw + sand + sawdust, T2: Sand + sawdust, T3: Straw + sawdust, T4: Sand, T5: Sawdust, T6: Straw, and T7: Control- over 84 days in the Eastern Terai region of Nepal. This research was conducted in a single-factorial Randomized Complete Block Design (RCBD) replicated thrice. Observations for physiological weight loss, sprouting, sprout length, insect incidence, rotting, and shrinkage percentage were recorded at 14-day intervals during the research. Results revealed that all storage materials significantly reduced post-harvest losses compared to the control (without storage material), with straw consistently outperforming all other treatments. Use of straw-based storage material significantly minimized physiological weight loss (19.6%), caused the shortest sprout length (1.31 cm), reduced shrinkage percentage (6.6%), minimal insect incidence (0.4%) and rotting (0.7%). This might be likely due to its insulating properties, moisture retention and ability to create a microenvironment which is unfavorable for pests and pathogens and favorable for moisture retention. A combination of straw with sand or sawdust also resulted in better results than the control, but straw alone consistently outperformed. These findings highlight straw as a locally available, environmentally friendly and cost-effective storage material is offering a practical and scientific strategy to enhance the shelf-life and postharvest quality of turmeric rhizome.